2018
DOI: 10.1128/jcm.00035-18
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Shedding of Five Genotypes of RotaTeq Vaccine Viruses by Genotype-Specific Real-Time Reverse Transcription-PCR Assays

Abstract: RotaTeq (RV5) is a widely used live attenuated pentavalent rotavirus (RV) vaccine. Although fecal shedding of RV vaccine strains persists for long time periods, it is unclear how each vaccine strain replicates in intestinal tissue and is excreted in stool. To examine this issue, we established RV5 genotype-specific real-time reverse transcription-PCR (RT-PCR) assays. Five real-time RT-PCR assays were designed for the VP7 gene in genotypes G1, G2, G3, G4, and G6. All assays exhibited excellent linearity, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(67 reference statements)
2
9
0
Order By: Relevance
“…Our recent study based on the RV5 G genotype‐specific real‐time RT‐PCR analysis suggested that patterns of fecal shedding of the five genotypes of vaccine viruses varied in vaccine recipients . Meanwhile, although RV5 contains five different genotypes, only G1 was detected in this patient.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our recent study based on the RV5 G genotype‐specific real‐time RT‐PCR analysis suggested that patterns of fecal shedding of the five genotypes of vaccine viruses varied in vaccine recipients . Meanwhile, although RV5 contains five different genotypes, only G1 was detected in this patient.…”
Section: Discussionsupporting
confidence: 93%
“…Viral double‐stranded RNA (dsRNAs) were extracted from the stool suspensions and 140 μL sera using a QIAamp Viral RNA Mini Kit (Qiagen, Hilden, Germany), following the manufacturer's instructions. RV5‐specific real‐time reverse transcription polymerase chain reactions (RT‐PCRs) were developed by our institute . PrimerQuest (Integrated DNA Technologies, Coralville, IA) was used to design primers and probes to differentiate between the VP7 genes (G1, G2, G3, G4, and G6) based on the reference sequences of the vaccine strains.…”
Section: Methodssupporting
confidence: 76%
See 2 more Smart Citations
“…The two licensed vaccines both include the G1 genotype, and G1 still remains a largely dominant G genotype worldwide [ 12 , 13 , 14 ]. It was also reported that G1 was the predominant shedding vaccine-related viral particle in vaccines [ 15 , 16 ], which may have an effect on the evolution of wild-type G1 circulating in populations. Thus, research on the long-term evolutionary characterizations of RVA G1 from a global perspective is desirable and is currently inadequate.…”
Section: Introductionmentioning
confidence: 99%